Incidencia de un sistema informático de composición de texto en la estandarización de los artículos científicos para la revista Enlace Universitario de la Universidad Estatal de Bolívar año 2016 - Costales Espinoza, Christian Alberto (2016)
The present investigation project seeks to determine the incidence of a computer system for the text composition in the standardization of the scientific articles for the magazine “Enlace Universitario” of the State University of Bolívar. Revised the literature related to this thematic one stands out that the investigated universities have digital repositories for the registration and discharge of publications; for what a computer tool was developed that will facilitate the elaboration of scientific articles on the part of the university community minimizing the times revision and correction, maintaining up-to-date the state of the document presented until obtaining the publication of the same one. For the development of the computer application it was contemplated the stages of software engineering; as well as the use of the method of the square Chi for the hypothesis confirmation based on the applied surveys to the sample specified in this project.